Prolonged fever in a 13-year-old girl misdiagnosed as Ochrobactrum spp. bacteremia-the pitfalls of diagnostic Brucella spondylitis in a non-endemic country - Smíšková, Dita; Smíšek, Petr; Nyč, Otakar (Folia microbiologica, 2025)
Brucellosis is a zoonosis with non-specific clinical symptoms involving multiple systems and organs. Its prevalence is low in most of EU countries, which can lead to the difficulties in laboratory and clinical diagnostic. Due to its relationship to the Ochrobactrum spp., it may be misclassified in rapid identification systems. We present a case of a 13-year-old immunocompetent girl who was examined several times for fever, fatigue, night sweats and weight loss; laboratory results showed mildly elevated C-reactive protein, anaemia and leukopenia. Four weeks before the onset of symptoms, she had been on a family holiday in Egypt. Given her symptoms, a haemato-oncological or autoimmune disease was considered more likely. The diagnosis of Brucella spondylitis was made after 4 months. The main reasons for this delay were as follows: low specificity of clinical symptoms, delay in completing the travel history, inconclusive initial serological results and misidentification of the blood culture isolate as Ochrobactrum sp. Even in countries with a low incidence of brucellosis, it is essential to educate healthcare professionals about the disease. Low specificity of symptoms and limited experience of laboratory staff may lead to late diagnosis with risk of complications and poor outcome. If Ochrobactrum spp. is detected in clinical specimens by rapid identification, careful re-evaluation must follow and all measures to prevent laboratory-acquired infections must be taken until Brucella spp. is unequivocally excluded.
Keywords: Gram-Negative Bacterial Infections; bakteriemie; Ochrobactrum; Humans; Female; Brucellosis; brucelóza; lidé; Fever; spondylitida; chybná diagnóza; Brucella; Bacteremia; horečka; ženské pohlaví; Spondylitis; Adolescent; Egypt; gramnegativní bakteriální infekce; Diagnostic Errors; mladiství